Effect of Orthodontic Treatment on Airway Dimensions in Patients with Obstructive Sleep Apnea: A Prospective Study - Mohammad K. Alam; Mohammad Y. Hajeer; Abdullah H. Alshammari; Saud A. A. Alshammari; Zeyad M. M. Alenezi (Journal of Pharmacy and Bioallied Sciences)
Background: Obstructive sleep apnea (OSA) is a common medical disorder characterized by recurrent instances of partial or total blockage of the upper airways while sleeping. Materials and Methods: The trial included a cohort of 50 individuals, aged between 18 and 45, who were diagnosed with mild to moderate obstructive sleep apnea (OSA). The participants were split into two groups: Group A (n = 25) had orthodontic therapy that included expanding the upper jaw and advancing the mandible, whereas Group B (n = 25) acted as the control group and did not get any orthopedic intervention. Prior to and after therapy, the airway dimensions were evaluated using cone beam computed tomography (CBCT) at two time points: baseline and 12 months after treatment. In this study, the main outcome measures were the change in airway volume (measured in mm3) and the minimum cross-sectional area (measured in mm2). The secondary outcome measures consisted of alterations in the apnea-hypopnea index (AHI) and subjective sleep quality evaluated by the Epworth Sleepiness Scale (ESS). Results: In comparison with baseline data, patients in Group A exhibited a statistically significant rise in airway volume (mean increase of 3500 mm3, P < 0.01) and minimum cross-sectional area (mean increase of 45 mm2, P < 0.01). In contrast, Group B exhibited no statistically significant alterations in these measures. A substantial decrease in AHI (mean reduction of 8 events/hour, P < 0.05) and an increase in ESS scores (mean improvement of 4 points, P < 0.05) were seen in Group A, suggesting improved sleep quality. Conclusion: Orthodontic treatment, including maxillary expansion and mandibular advancement, positively affects airway dimensions in patients with OSA.